2001
DOI: 10.1007/bf03014965
|View full text |Cite
|
Sign up to set email alerts
|

Spainal anesthesia improves the early recovery profile of patients undergoing ambulatory knee arthroscopy

Abstract: SA with 50 mg of 1% lidocaine provides an improved recovery profile for ambulatory knee arthroscopy. Discharge times were similar, and with the exception of backache and sore throat, the incidence of complications was similar.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0
2

Year Published

2001
2001
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 20 publications
1
24
0
2
Order By: Relevance
“…[1][2][3][4] Local anesthetics with fast onset, fast offset, and minimal adverse effects have been an area of interest for anesthesiologists, surgeons, and hospital administrators alike in order to ensure timely discharge following day surgery. Ambulation is the most important postoperative milestone affecting a patient's home readiness and ultimately discharge from hospital.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Local anesthetics with fast onset, fast offset, and minimal adverse effects have been an area of interest for anesthesiologists, surgeons, and hospital administrators alike in order to ensure timely discharge following day surgery. Ambulation is the most important postoperative milestone affecting a patient's home readiness and ultimately discharge from hospital.…”
Section: Introductionmentioning
confidence: 99%
“…4 Ad van ta ges of spi nal anest he si a inc lu de ra pid on set of sen sory and mo tor block, pre dic table ef fi cacy and prompt reg res si on. 12,13 In a ran domi zed cli ni cal tri al of pe ri a nal sur gery, Schmitt ner et al 14 re por ted that sadd le block was su pe ri or to to tal in tra ve no us anest he si a in terms of anal ge sic con sump ti on wit hin 24 ho urs af ter sur gery and aspects of pos to pe ra ti ve re co very. Des pi te se ve ral advan ta ges of spi nal anest he si a, mo tor block, si de ef fects such as hypo ten si on and uri nary re ten ti on may be the ca u ses of de la yed disc har ge from PA CU and the hos pi tal.…”
Section: Discussionmentioning
confidence: 99%
“…Other authors 15 have described difficult CSF aspiration resulting in blockade failure, what has also been observed in our study. Comparing spinal anesthesia with 50 mg of 1% lidocaine and general anesthesia for outpatient knee arthroscopy it has been observed that spinal anesthesia has provided faster recovery and better postoperative analgesia 16 . In the conditions of our study, 0.5% isobaric S75-R25 bupivacaine has induced adequate and safe anesthesia in patients aged 1 to 5 years for outpatient procedures.…”
Section: Demographicmentioning
confidence: 99%
“…Outros autores 15 descreveram dificuldade de aspiração do LCR resultando em falha no bloqueio, fato também observado no nosso estudo. Comparando a raquianestesia com 50 mg de lidocaína a 1% e anestesia geral para artroscopia de joelho em regime ambulatorial observou-se que a raquianestesia proporcionou uma recuperação mais rápida e analgesia pós-operatória de melhor qualidade 16 . Nas condições deste trabalho a mistura enantiomérica de bupivacaína (S75-R25) 0,5% isobárica produziu anestesia adequada e segura em pacientes de 1 a 5 anos em regime ambulatorial.…”
unclassified